2004
DOI: 10.1002/jbm.a.30061
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of different preparations of plasma‐sprayed hydroxyapatite coatings on Ti6Al4V substrate

Abstract: The corrosion behavior of four different preparations of plasma-sprayed hydroxyapatite (HA) coatings on Ti6Al4V substrates in static Hank's balanced salt solution was investigated using dc potentiodynamic and ac impedance techniques. Two different nominal thicknesses, 50 microm and 200 microm, and two different spraying conditions, were considered. The electrochemical impedance experiments proved this technique to be very suitable for the investigation of the electrochemical behavior of surgical implant alloys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…[157] investigated the corrosion behavior of four different preparations of plasma-sprayed hydroxyapatite (HA) coatings (50 μm and 200 μm) on Ti-6Al-4V substrates in static Hank’s balanced salt solution through DC potentiodynamic and AC impedance EIS techniques. Because the coatings are porous, ionic paths between the electrolytic medium and the base material can eventually be produced, resulting in the corrosion of the coated metal.…”
Section: Surface Texturingmentioning
confidence: 99%
See 1 more Smart Citation
“…[157] investigated the corrosion behavior of four different preparations of plasma-sprayed hydroxyapatite (HA) coatings (50 μm and 200 μm) on Ti-6Al-4V substrates in static Hank’s balanced salt solution through DC potentiodynamic and AC impedance EIS techniques. Because the coatings are porous, ionic paths between the electrolytic medium and the base material can eventually be produced, resulting in the corrosion of the coated metal.…”
Section: Surface Texturingmentioning
confidence: 99%
“…Because the coatings are porous, ionic paths between the electrolytic medium and the base material can eventually be produced, resulting in the corrosion of the coated metal. It was concluded that significant differences were found in electrochemical behavior for similar nominal thicknesses of HA coatings obtained under different spraying [157]. Filiaggi et al .…”
Section: Surface Texturingmentioning
confidence: 99%
“…However, bone does not bond directly to these materials, therefore, in order to enhance the bone-bonding ability, titanium and its alloys are often coated with HA by various methods. Hence the combination of nano-TiO 2 and nano-HA coating on 316L SS may be used as an alternative in orthopedic appliances, providing a competitive and low cost alternative related to highly expensive conventional Co-Cr and Ti alloys [3,41,53].…”
Section: Preparation Of Osteoconductive Metallic Implantsmentioning
confidence: 99%
“…El termino biomaterial fue tomado inicialmente para describir un material que podría ser utilizado para reemplazar huesos y tejidos enfermos o dañados en un organismo vivo, ( Williams, 1987); sin embargo el trabajo interdisciplinario ha hecho que la definición sea más amplia; en ese sentido, los biomateriales pueden ser considerados como productos aptos para ser utilizados en los seres humanos con fines de tratamiento o alivio de una enfermedad, lesión o bien para sustitución o modificación de su anatomía o de un proceso fisiológico (Enderle, 2005;Souto et al, 2003); es por esto que se han desarrollado diferentes materiales que puedan suplir los requerimientos físicos, químicos y biológicos para un perfecto funcionamiento que garanticen las mejores condiciones de trabajo y los mejores resultados (Geringer et al, 2013;García et al, 2004). En el campo de los biomateriales puede hacerse una clasificación primaria por la naturaleza del material: Biometales, Biopolímeros, cerámicos; a pesar de sus diferencias, su principal propiedad es la de no generar residuos tóxicos en la interacción con el organismo.…”
Section: Introductionunclassified